Understanding Gen Z’s Climate Anxiety: A Look at the Latest Research - FutoJudit Edit; Karcagi-KovatsAndrea; SzendreyOrsolya; HarazinPiroska; PintyeLili Mirella; GulyasDavid (Cognitive Sustainability, 2024)
Nowadays, the widespread availability of information on climate change has made up-to-date knowledge in this area more accessible to a broad section of society. At the same time, this information overload can potentially threaten psychological well-being. In particular, a specific form of anxiety, commonly known as climate (change) anxiety, is a substantial problem. Although climate anxiety terminology only became commonplace a few years ago, the phenomenon itself has older roots. It includes several responses to climate change, the complexity of which assumes more detailed knowledge. The fact that climate disasters are becoming more common may generate intense negative emotions such as fear, depression, tension, and rage. According to current studies, stress derived from climate change is most prevalent among Generation Z. This generation group is the focus of researchers due to their outstanding environmentally conscious approach. They are possibly expected to make the most important decisions in the future, and worries about climate change may significantly influence their decisions. Researchers need to analyze the multiple causes of this phenomenon and the actions they induce. This economic literature review aims to summarize the main observations from the international literature in this field.